2023
DOI: 10.1002/tox.23728
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naringin on oxidative stress, inflammation, some reproductive parameters, and apoptosis in acrylamide‐induced testis toxicity in rat

Abstract: Acrylamide (ACR) is used in many fields such as cosmetics, paper, and textile industries. It also occurs at very high temperatures in some foods. Gonadotoxic effects of ACR have been found in experimental animals. Many studies use flavonoids to prevent the reproductive side effects of ACR. Naringin (NA) is a flavonoid and it has been determined by studies that it has no toxic effect on tissues. In our study, we aimed to determine the protective effect of NA against the damage of ACR on testicular tissue and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Numerous studies have suggested that inflammation and oxidative stress play an important role in the pathophysiology of various diseases, such as lung, testis, liver, thyroid, and kidney toxicity and pulmonary fibrosis 34–44 . Moreover, emerging findings exhibited that Cat has obvious anti‐inflammatory, antioxidant, and antiapoptotic properties and its vital protective function in multiple organ damage 45,46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have suggested that inflammation and oxidative stress play an important role in the pathophysiology of various diseases, such as lung, testis, liver, thyroid, and kidney toxicity and pulmonary fibrosis 34–44 . Moreover, emerging findings exhibited that Cat has obvious anti‐inflammatory, antioxidant, and antiapoptotic properties and its vital protective function in multiple organ damage 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is essential to reveal the pathogenesis of SAKI, thereby paving the way for the develop- pulmonary fibrosis. [34][35][36][37][38][39][40][41][42][43][44] Moreover, emerging findings exhibited that Cat has obvious anti-inflammatory, antioxidant, and antiapoptotic properties and its vital protective function in multiple organ damage. 45,46 For instance, Xia et al manifested that Cat protected the spinal cord from spinal cord injury in mice through mediating microRNA-142-mediated HMGB1/TLR4/NF-κB signaling pathway.…”
Section: Cat Relieves Renal Damage Via Upregulating Sirt1 By Activati...mentioning
confidence: 99%
“…11 In addition, recent studies have linked increased oxidative stress, inflammation, and apoptosis to AA-induced reproductive toxicity. 40,41 These studies were performed on whole testes and little is known regarding the potential testicular target cells of AA, such as spermatocytes, and their involvement in meiosis and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…for 10 consecutive days. 28,29 Se0.5 + ACR group: Rats received a daily dose of Se (0.5 mg/kg, i.g.) 13 followed by a daily dose of ACR (40 mg/kg) (i.p.)…”
Section: Experimental Designmentioning
confidence: 99%
“…Se1 + ACR groups: Rats received a daily dose of Se (1 mg/kg, i. g.) 13 followed by a daily dose of ACR (40 mg/kg, i.p.) 28,29 for 10 consecutive days.…”
Section: Experimental Designmentioning
confidence: 99%